Variation of extractable compounds and lignin contents in wood fragments used in the aging of wine brandies - Anjos, O. (2013)
Submitted by Maria Eduarda Pereira Rodrigues (erodrigues@ipcb.pt) on 2013-07-18T15:13:04Z No. of bitstreams: 1 Anjos_2013_Variation_Extractable_Lignin_Wood_Aging_Brandies.pdf: 456946 bytes, checksum: 52e5e2c76b8a4c096d806ccaa413fbae (MD5)